2002
DOI: 10.1007/s100670200077
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound and Clinical Evaluation of Quadricipital Tendon Enthesitis in Patients with Psoriatic Arthritis and Rheumatoid Arthritis

Abstract: Enthesitis is an inflammatory lesion of the tendon, ligament and capsular insertions into the bone, and it is a fundamental element in the diagnosis of spondyloarthropathies. Sonography is the method of choice for studying periarticular soft tissues because it is capable of detecting both the early (oedema, thickening) and late alterations (erosions and enthesophytes); it is also an inexpensive, biologically harmless and easily repeatable technique. The aim of this study was to compare the prevalence of quadri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(32 citation statements)
references
References 0 publications
3
29
0
Order By: Relevance
“…Histological findings from cadavers indicate the underlying structural changes at and around the enthesis including periosteal bone reaction, alterations of the bone structure, and increased bone formation, endochondral ossification, and vascular invasion of the fibrocartilage that facilitates access for inflammatory cells [37]. Our results are in agreement with Balint et al who demonstrated thickening on US of the infrapatellar and tibial entheseal insertions in patients with SpA [38], and with other authors describing tendon thickening on US in SpA [11, 39]. …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Histological findings from cadavers indicate the underlying structural changes at and around the enthesis including periosteal bone reaction, alterations of the bone structure, and increased bone formation, endochondral ossification, and vascular invasion of the fibrocartilage that facilitates access for inflammatory cells [37]. Our results are in agreement with Balint et al who demonstrated thickening on US of the infrapatellar and tibial entheseal insertions in patients with SpA [38], and with other authors describing tendon thickening on US in SpA [11, 39]. …”
Section: Discussionsupporting
confidence: 91%
“…The main drivers of the local inflammatory process are TNF- α , interleukin-1 (IL-1) and IL-6 which produce proteolytic enzymes such as matrix metalloproteinases that lead to collagen destruction [32], and the proangiogenic vascular endothelial growth factor, which evokes synovial hyperplasia and infiltration of macrophages and T cells into synovium [14]. According to the different pathologies of RA and AS inflammatory molecules target primarily the enthesis in AS, whereas in RA tendon involvement is thought to be secondary through the proximity to inflamed synovium [10, 11]. Systemically circulating cytokines [33] could have an additional detrimental effect on the tendon in both RA and AS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MRI and US, especially with the aid of contrast, offer a unique advantage over conventional radiography in the evaluation of enthesopathy, a prominent clinical feature of PsA, as well as in the assessment of sacroiliitis. These techniques can better distinguish the presence and extent of inflammatory activity in these lesions, and potentially may be sensitive tools for assessing the response to therapy (82)(83)(84)(85)(86). The assessment of entheses is particularly important in PsA, since its role in the pathogenesis of the disease has been emphasized (87).…”
Section: Imaging Methodsmentioning
confidence: 99%
“…According to this hypothesis, synovitis in PsA is considered to be secondary to the extra-capsular disease. On the other hand, a number of authors have recognised the occurrence of enthesitis as part of the RA disease spectrum [6–8]. It is therefore clear that, by the time the patient presents, both synovitis and enthesitis may occur in both conditions, occasionally making it difficult to distinguish between them on radiological grounds [9].…”
Section: Introductionmentioning
confidence: 99%